Kredibilitas Tasya Farasya sebagai Influencer terhadap Minat Pembelian Produk Skincare melalui Kepercayaan Konsumen Pada Gen Z - Diva Intan Jelita S Putri; Ida Bagus Raka Suardana (Jurnal Ekonomi dan Industri, 2025)
This study is motivated by the growing use of social media as a primary channel for beauty product promotion, where influencers play a crucial role in shaping consumer perception and purchase intention, particularly among Generation Z. Influencers such as Tasya Farasya possess high credibility, which can significantly influence audience trust and buying behavior. The originality of this study lies in its focus on examining the relationship between influencer credibility, consumer trust in influencers, and purchase intention in the skincare context, with trust serving as a mediating variable. The aim of this research is to analyze the effect of influencer credibility on consumer purchase intention and to test the mediating role of trust among Gen Z followers. A quantitative method was employed through a survey of Tasya Farasya’s social media followers, and the data were analyzed using Partial Least Square-Structural Equation Modeling (PLS-SEM). The empirical findings reveal that influencer credibility has a positive and significant impact on consumer trust, and that trust partially mediates the relationship between influencer credibility and purchase intention. Thus, higher perceptions of influencer expertise, integrity, and attractiveness enhance consumer trust and subsequently increase purchase intention toward the promoted skincare products. Tactically, this study implies that beauty industry practitioners should optimize their influencer marketing strategies by emphasizing authenticity, transparency, and trust-building to effectively engage the more critical and selective Gen Z market.